Comparative analysis of medical and social characteristics of women with malignant and benign breast neoplasms: the impact of medical and social determinants of public health - A. A. Sukhov; S. N. Cherkasov; S. V. Russkikh; A. V. Fedyaeva; S. S. Saidov; Е. А. Tarasenkо (Сибирский научный медицинский журнал, 2025)
Medical and social determinants of public health influence the state of health, risk of occurrence and outcomes of breast neoplasms in women.   The aim of the study is a comparative analysis of medical and social characteristics of women with malignant and benign breast neoplasms.   Material and Methods. The data of a survey of 600 female patients were used. The main group (women with malignant breast neoplasms) and the control group (women with benign breast neoplasms) were compared, the data were obtained during the survey and by copying data from medical records. The medico-social attributes were combined into groups.   Results and discussion. Despite the fact that the groups are similar in social status and lifestyle, data on the presence of evidentiary differences between them in the main groups of characteristics (four groups of characteristics were taken into account: “Obstetric history”; “Morbidity”; “Social status”; “Lifestyle”) were obtained.      Conclusions. The social trait “loneliness” through obstetric history is associated with the incidence of breast malignancy. Screening in groups of women with malignant and benign breast neoplasms should be conducted separately, taking into account the social determinant – the social and economic conditions in which they live and are treated, and also in the context of the medical determinant, which includes consideration of the level of professional competence of medical personnel who diagnose and treat these diseases.